(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This paper represents an analytical resource of the phenomenon of political personalization in electoral campaigns, from the accommodation of political forces in polyarchic systems. In this way, it is based on Robert Dahl's proposal by considering that democratic government systems are, rather, polyarchies and that a multitude of interests, starting points and political forces converge in them that have led to a kind of re-understanding. of the relationship of candidates and political parties in order to continue to be valid in the political arena and win the citizen vote. The central thesis of the paper is that political personalization should not only be understood as the maximization of the personal attributes of those who aspire to win electoral contests, but also as a result of the loss of partisan identities in an increasingly plural and diverse sociopolitical context. . Therefore, the main objective of the document is to establish an analytical route that favors the understanding of political personalization as a result of a complex network of political circumstances that have promoted electoral campaigns that tend to maximize personal qualities and attributes within the framework of polyarchic systems.